2022
DOI: 10.1111/aos.15195
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and severity of cornea guttata in the graft following Descemet Membrane Endothelial Keratoplasty (DMEK)

Abstract: Purpose: The aim of this study was to determine the prevalence and severity of cornea guttata (CG) in grafts after Descemet membrane endothelial keratoplasty (DMEK) and to investigate its impact on various clinical parameters during follow-up. Methods: This retrospective study included 664 operations (DMEK and triple-DMEK) on 466 patients. The prevalence and progression of CG after the operation were examined using endothelial specular microscopy images. The severity grade of CG was classified into four grades… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 41 publications
1
6
0
Order By: Relevance
“…keratoplasty (PK), corneal guttae were observed in 13% to 26% of the grafts, 6,10,15 for Descemet stripping automated endothelial keratoplasty (DSAEK) in 3% of the grafts (from the same study that reported a rate of 13% after PK), 6 and for DMEK in 4% to19% of the eyes. 11,14 Occurrence of corneal guttae in this case series could be detected within the first postoperative month which corroborates previous reports on the early guttae occurrence after DSAEK and DMEK. 9,11 Along with the fact that corneal guttae have been observed for patients with surgery indications other than FECD, [6][7][8][9][10]12,15 this supports the hypothesis that the corneal guttae originate from the donor tissue.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…keratoplasty (PK), corneal guttae were observed in 13% to 26% of the grafts, 6,10,15 for Descemet stripping automated endothelial keratoplasty (DSAEK) in 3% of the grafts (from the same study that reported a rate of 13% after PK), 6 and for DMEK in 4% to19% of the eyes. 11,14 Occurrence of corneal guttae in this case series could be detected within the first postoperative month which corroborates previous reports on the early guttae occurrence after DSAEK and DMEK. 9,11 Along with the fact that corneal guttae have been observed for patients with surgery indications other than FECD, [6][7][8][9][10]12,15 this supports the hypothesis that the corneal guttae originate from the donor tissue.…”
Section: Discussionsupporting
confidence: 91%
“…10,15 For DMEK, also no effect of guttae on graft survival was reported. 14 In our case series, 2 of 13 grafts (15%) failed, but because this is a small case series, this might not be representative for the actual graft survival probability in the presence of guttae, which might be comparable to the graft survival probability observed in a large DMEK cohort (90% at the 5-year follow-up and 85% at the 10-year follow-up). 22 Corneal guttae are known to affect endothelial cells, 3 but the effect of the observed corneal guttae on postoperative ECD is difficult to quantify because endothelial cell counts on specular microscopy images in the presence of corneal guttae do not tend to be reliable due to a high degree of variability in cell density.…”
Section: Discussionmentioning
confidence: 67%
See 3 more Smart Citations